Seeing beauty & saying beautifully : the power of poetic effort : George Herbert, George Whitefield and C.S. Lewis /: the power of poetic effort : George Herbert, George Whitefield and C.S. Lewis. (2014) - Piper, John, 1946-
No abstract available